2005
DOI: 10.1242/dev.01792
|View full text |Cite
|
Sign up to set email alerts
|

Hym-301, a novel peptide, regulates the number of tentacles formed in hydra

Abstract: Hym-301 is a peptide that was discovered as part of a project aimed at isolating novel peptides from hydra. We have isolated and characterized the gene Hym-301, which encodes this peptide. In an adult, the gene is expressed in the ectoderm of the tentacle zone and hypostome, but not in the tentacles. It is also expressed in the developing head during bud formation and head regeneration. Treatment of regenerating heads with the peptide resulted in an increase in the number of tentacles formed, while treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 60 publications
4
39
0
Order By: Relevance
“…This possibility was the motivation for the Hydra peptide project (Takahashi et al, 1997;Fujisawa, 2008), which had the goal of identifying novel peptides involved in developmental processes in Hydra (Fujisawa and Hayakawa, 2012). This project has led to the identification of the Hym-301 peptide, which is involved in head formation, Hym-355 and the PW peptides, which play stimulatory and inhibitory roles, respectively in nerve cell differentiation, and Hym-346 and Hym-323 peptides, which have roles in foot formation (Grens et al, 1999;Takahashi et al, 2000;Takahashi et al, 2005;. Although Hayakawa et al, (2007) have shown that a computational approach can be used to identify potential precursors to peptides in Hydra in ESTs or in gene models from the Hydra genome, functional screens of the sort developed by the Hydra Peptide Project clearly still have a role to play in defining the molecules that control developmental processes in Hydra, with the genome sequence playing an enabling role.…”
Section: What Genes Are Novel?mentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility was the motivation for the Hydra peptide project (Takahashi et al, 1997;Fujisawa, 2008), which had the goal of identifying novel peptides involved in developmental processes in Hydra (Fujisawa and Hayakawa, 2012). This project has led to the identification of the Hym-301 peptide, which is involved in head formation, Hym-355 and the PW peptides, which play stimulatory and inhibitory roles, respectively in nerve cell differentiation, and Hym-346 and Hym-323 peptides, which have roles in foot formation (Grens et al, 1999;Takahashi et al, 2000;Takahashi et al, 2005;. Although Hayakawa et al, (2007) have shown that a computational approach can be used to identify potential precursors to peptides in Hydra in ESTs or in gene models from the Hydra genome, functional screens of the sort developed by the Hydra Peptide Project clearly still have a role to play in defining the molecules that control developmental processes in Hydra, with the genome sequence playing an enabling role.…”
Section: What Genes Are Novel?mentioning
confidence: 99%
“…As expected for a gene putatively involved in head formation, polyps exposed to the ks1 dsRNA showed marked delays in head regeneration. RNAi carried out by electroporation has been used to study the functions of additional Hydra genes (Lohmann and Bosch, 2000;Smith et al, 2000;Cardenas and Salgado, 2003;Takahashi et al, 2005;Amimoto et al, 2006;Khalturin et al, 2008), and a method has now been developed for carrying out RNAi in Hydra by feeding the animals bacteria producing dsRNA for the target gene (Chera et al, 2006;Miljkovic-Licina et al, 2007;Chera et al, 2009;Chera et al, 2011). Despite these efforts, RNAi is not yet a robust, widely used technology for functional studies in Hydra.…”
Section: Introductionmentioning
confidence: 99%
“…Directly cooperating with the immediate cell-to-cell signalling of Notch-and ephrin pathways, are FGF-and Wnt-signalling pathways (Takahashi et al, 2005). Both pathways depend on diffusible ligands and membrane-bound receptors and are thus able to integrate signals, which move across longer distances.…”
Section: Signalling Involving Diffusible Moleculesmentioning
confidence: 99%
“…Slightly beyond this Wnt3 zone reaches expression of the Wnt-targeted transcription factor, HyTcf (Hobmayer et al, 2000). An even larger area including the entire hypostome and almost touching the bases of tentacles is covered by HyBra expression (Technau and Bode 1999), its expression domain overlaps with HyWnt7 (Lengfeld et al, 2009) and transcription factors like budhead and prdl-a (Martinez et al, 1997;Gauchat et al, 1998;Takahashi et al, 2005). The region where hypostome cells proliferate is marked by the expression of budhead, which is lacking underneath the proliferative region, but is present again in the space between the tentacles.…”
Section: Head and Upper Body Regionmentioning
confidence: 99%
See 1 more Smart Citation